IGARSS 2001. Scanning the Present and Resolving the Future. Proceedings. IEEE 2001 International Geoscience and Remote Sensing
DOI: 10.1109/igarss.2001.976223
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric measurements of the microwave emissivity of foam

Abstract: Abstract-Radiometric measurements of the microwave emissivity of foam were conducted during May 2000 at the Naval Research Laboratory's Chesapeake Bay Detachment using radiometers operating at 10.8 and 36.5 GHz. Horizontal and vertical polarization measurements were performed at 36.5 GHz; horizontal, vertical, +45 , 45 , left-circular, and right-circular polarization measurements were obtained at 10.8 GHz. These measurements were carried out over a range of incidence angles from 30 to 60 . Surface foam was gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 13 publications
7
36
0
Order By: Relevance
“…Moreover, in Figure 6 we have calculated the emissivity of the foam layer with a foam thickness of 2.8 cm and compared it with the experimental data of E.-B. Wei Rose et al (2002) for frequencies 10.8 and 36.5 GHz, obtaining good agreement. With the above investigations, it is concluded that the uniform medium method of averaged effective permittivity is feasible to deal with the graded foam layer of vertical profile.…”
Section: Emissivity Model Of a Vertical Graded Foam Layermentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, in Figure 6 we have calculated the emissivity of the foam layer with a foam thickness of 2.8 cm and compared it with the experimental data of E.-B. Wei Rose et al (2002) for frequencies 10.8 and 36.5 GHz, obtaining good agreement. With the above investigations, it is concluded that the uniform medium method of averaged effective permittivity is feasible to deal with the graded foam layer of vertical profile.…”
Section: Emissivity Model Of a Vertical Graded Foam Layermentioning
confidence: 72%
“…Microwave emissivity of a foam layer has been discussed using wind speed, foam structure, and the effective medium approximation (EMA) model (Droppleman 1970;Militskii et al 1978;Wilheit 1979). Recently, the emissivities of a foam layer were measured at 10.8, 36.5, and 1.4 GHz for different foam layer thicknesses, sea surface temperatures (SSTs), and sea surface salinities (SSSs), respectively (Rose et al 2002;Camps et al 2005). In addition, Williams (1971) conducted an experiment to discuss the effect of foam layer thickness on emissivity.…”
Section: Introductionmentioning
confidence: 98%
“…If the sea surface is completely covered by foams, in Figure 3, we have compared our results with Rose's experimental data. In this figure, the SSE changes with the incident angle at both frequencies 10.8 GHz and 36.5 GHz, where the solid line and dotted line denote the results of vertical and horizontal polarizations, respectively, and the circle and the cross are Rose's experimental values for horizontal and vertical polarization directions, respectively [24] . Clearly, comparing our results with experimental data, a good agreement is obtained.…”
Section: Results Of the Modelmentioning
confidence: 99%
“…When the value of wind speed is larger than 7 m/s, there exists a whitecap layer produced by broken waves, where the whitecaps layer consists of the bubbles and seawater droplets. For the temperature 292 K and the salinity 10 of seawater, Rose et al [24] obtained a set of SSE data by experimental measurement for foam layer thickness 2.8 cm and at microwave frequencies 10.8 GHz and 36.5 GHz, where the seawater surface is completely covered by the foam layer. In this case, they observed that the value of SSE is larger than 0.9 and will be a constant if the incident angle changes from 30° to 60° at the vertical polarization direction.…”
Section: Results Of the Modelmentioning
confidence: 99%
“…Wind roughening of the ocean in form of small scale (capillary) waves, large scale (gravity) waves, and whitecaps (with resulting foam) allow such instruments to remotely sense the wind vector. However, near-surface radiometric observations are still very much needed to improve the quantitative knowledge of the effects of changing surface conditions, including foam and roughness, on microwave emissivity [1].…”
Section: Introductionmentioning
confidence: 99%